Acute effects of amphetamine and related psychostimulants on impulsivity: a systematic review of clinical trials. (18th January 2022) - Arkell, Thomas R.; Bradshaw, Kristina; Downey, Luke A.; Hayley, Amie C.
Abstract: Evidence for acute amphetamine effects on behavioural impulsivity in healthy populations remains elusive and, at times, mixed. This review collates and reviews the clinical literature on the acute effects of amphetamines on measures of behavioural impulsivity in healthy adults. Randomised and placebo‐controlled clinical trials that assessed behavioural impulsivity following the administration of an acute dose of amphetamine or a related psychostimulant (including amphetamine analogues and methylphenidate) were eligible for inclusion. The EBSCOHost, SCOPUS, PsychNet, Web of Science and ProQuest databases were searched from inception to 26 April 2021. Study selection, data extraction and the Cochrane risk of bias assessments were conducted by two independent reviewers. Reporting follows PRISMA guidelines, and the review was registered a priori on the PROSPERO database (Registration No: CRD42021249861). A total of 20 studies were included, comprising a total of 737 participants. Overall, results indicate that low‐moderate doses of amphetamine and related psychostimulants may improve (i.e., reduce) impulsive responding without compromising performance, reflecting enhanced inhibitory control of behaviour. These effects are mild and appear most pronounced in individuals with high baseline impulsivity. This review highlights the need for greater consistency in behavioural task selection and future high‐quality and well‐designed studies to address current concerns around growing prescription psychostimulant use and misuse. Abstract : This systematic review identified 20 randomised clinical trials which administered an acute dose of amphetamine or a related substance to healthy adults. Overall, studies tended to report mild but positive drug effects on impulsive responding, reflecting enhanced inhibitory control of behaviour. This review highlights the need for greater consistency in behavioural task selection in future studies.